Pesticide Recordkeeping Form for Florida Applicators - Frederick M. Fishel (EDIS, 2019)
This 5-page document provides a form containing the required elements to include on a record of pesticide application for meeting the restricted use pesticide and Worker Protection Standard (WPS) requirements. An example application record and an explanation of the required elements is provided. This is not a required form because there are other methods to keep records if they contain the required information. Handwritten notes, electronic records, and other recordkeeping software systems are also acceptable. Written by Frederick M. Fishel and published by the UF/IFAS Agronomy Department. http://edis.ifas.ufl.edu/pi280